Picicola Clay and Meinertzhagen (Phthiraptera: Philopteridae) from jacamars and puffbirds (Piciformes: Galbulidae, Bucconidae), with descriptions of five new species - Price, Roger D.; Weckstein, Jason D. (Zootaxa, 2006)
The three species of previously named Picicola Clay and Meinertzhagen from jacamars and puffbirds are redescribed and five new species are described and illustrated. These new species and their type hosts are: Picicola valquii ex Notharchus tectus (Boddaert), P. naokii ex Bucco capensis Linnaeus, P. osheai ex Malacoptila fusca (J.F. Gmelin), P. faucetti ex Chelidoptera tenebrosa (Pallas), and P. oneilli ex Notharchus macrorhynchos (J.F. Gmelin). We collected partial cytochrome oxidase I (COI) sequences for all of the species in this group, and these data support the genetic distinctiveness of these new species. A key is provided for the identification of all eight species of Picicola from jacamars and puffbirds.